2014
DOI: 10.1371/journal.pone.0096211
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin A (CypA) Interacts with NF-κB Subunit, p65/RelA, and Contributes to NF-κB Activation Signaling

Abstract: BackgroundPeptidyl-prolyl isomerase cyclophilin A (CypA) plays important roles in signaling, protein translocation, inflammation, and cancer formation. However, little is known about the mechanisms by which CypA exerts its effects. C57BL/6 Ppia (encoding CypA)-deficient embryonic fibroblasts show reduced activation of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), the p65/RelA subunit, suggesting that CypA may mediate modulation of NF-κB activity to exert its biological effects.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 38 publications
1
45
0
Order By: Relevance
“…However, the functional role of the closely related PPIase family member CypA (PPIA) in skeletal development remains elusive. In previous reports, we demonstrated a close relationship between CypA and NF-B signaling (22,28). NF-B was found to regulate certain aspects of endochondral ossification during embryogenesis (29,30).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…However, the functional role of the closely related PPIase family member CypA (PPIA) in skeletal development remains elusive. In previous reports, we demonstrated a close relationship between CypA and NF-B signaling (22,28). NF-B was found to regulate certain aspects of endochondral ossification during embryogenesis (29,30).…”
Section: Discussionmentioning
confidence: 66%
“…We had previously demonstrated that CypA knockdown (Kd) results in the downregulation of NF-B/p65 (RelA, a subunit of NF-B) in glioblastoma cell lines and a murine myoblast line, C2C12 (22,28). Decreased NF-B/p65 expression levels were also observed in CypA Kd mouse chondrogenic ATDC5 stable clones, 2T7 and 2T3, as well as in CypA KO mouse proximal tibia growth plates ( Fig.…”
Section: Effect Of Cypa Deficiency On Chondrocyte Differentiation In mentioning
confidence: 90%
See 1 more Smart Citation
“…For example, the stability, localisation and activity of the p65 subunit of NF-κB was recently shown to be regulated by association with CypA because its downregulation impaired production of NF-κB-induced cytokines while reducing the proliferation of glioblastoma cells. 32,33 Similar to CypA, genetic ablation of CypB reduces glioma cell survival and proliferation, as shown both in vitro and in vivo. 34,35 We found that multiple cyclophilins -CypA, CypB and CypH -directly interact with a newly identified target, p38MAPK, facilitating isomerisation of Pro224, which in turn is required to regulate phosphorylation of kinase regulatory Thr-Gly-Tyr motif.…”
Section: Discussionmentioning
confidence: 90%
“…It can inhibit IL-4 induction by Itk (Colgan et al, 2004) and regulates the RA-induced neuronal differentiation (Song et al, 2004). Moreover, CypA may also facilitate the interleukin-6 (IL-6)-induced signal transducer and activation of transcription 3 (Stat3) tyrosine phosphorylation and nuclear translocation (Bauer et al, 2009), and can strongly associate and activate NF-kB in vitro and in vivo (Obchoei et al, 2009;Sun, et al 2014).…”
Section: Introductionmentioning
confidence: 99%